Diasporic modernisms Hebrew and Yiddish literature in the twentieth century - Schachter, Allison, 1974- (New York ; Oxford : Oxford University Press, 2012)
'Diasporic Modernisms' illuminates the formal and historical aspects of displaced Jewish writers - S.Y. Abramovitsh, Yosef Chaim Brenner, Dovid Bergelson, Leah Goldberg, and others - who grappled with statelessness and the uncertain status of Yiddish and Hebrew.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Mendele Mokher Sefarim, -- 1835-1917 -- Criticism and interpretation; Bergelson, David, -- 1884-1952 -- Criticism and interpretation; Goldberg, Leah, -- 1911-1970 -- Criticism and interpretation; Hebrew literature, Modern -- 20th century -- History and criticism; Yiddish literature -- 20th century -- History and criticism; Modernism (Literature)